Glucagon-like Peptide-1 Analogues Inhibit Proliferation and Increase Apoptosis of Human Prostate Cancer Cells in vitro - Li, X.-n.; Bu, H.-m.; Ma, X.-h.; Lu, Sh.; Zhao, Sh.; Cui, Y.-l.; Sun, J. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background: Research has shown that the incidence of prostate cancer is increased in patients with type 2 diabetes mellitus (T2DM) 1. Glucagon-like peptide-1 (GLP-1) is a gastrointestinal hormone that enhances glucose-dependent insulin secretion and suppresses glucagon release.Method: Here, we examined the effect of exenatide and liraglutide, 2 types of GLP-1 analogues, on prostate cancer cells growth by CCK-8 assay, Hoechst33258 staining assay, and western blot analysis of apoptosis-related proteins Bax and Bcl-2. Also the kinase pathways maybe involved and the expression of GLP-1 receptor (GLP-1 R) in LNCap cells was detected.Results: In our experiments, exenatide and liraglutide significantly inhibited the proliferation of the LNCap cell lines and induced the cell apoptosis. Exenatide (1–100 nmol/L) increased the ratio of Bax/Bcl-2 in a dose-dependent manner, whereas liraglutide increased Bax/Bcl-2 ratio only at concentrations of 10 nmol/L. And we found that GLP-1 analogues activate p38 but not ERK1/2 or AKT in LNCap cells. And classical GLP-1 receptor was detected in LNCap cells.Conclusion: These data suggest that exenatide and liraglutide attenuate prostate cancer growth through regulating P38 pathway by binding with GLP-1R.
Keywords: prostate cancer; glucagon-like peptide-1; LNCap; apoptosis; proliferation